1978
DOI: 10.3109/03009747809095660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical, Radiation and Surgical Synovectomy for Knee Joint Synovitis

Abstract: In 66 patients with rheumatoid knee joint synovitis and hydrops and with only slight radiological destruction, local treatment of the knee was randomly performed either with osmic acid, radioactive yttrium or surgical synovectomy. After a one-year follow-up the clinical and radiological results were slightly better in patients who underwent surgical synovectomy than in other treatment groups. However, radiological osteoarthrosis had progressed more in synovectomized patients than in others. In 2 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
2

Year Published

1981
1981
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 7 publications
1
4
0
2
Order By: Relevance
“…The tentative conclusion from this study then is that Os04 in doses corresponding to those used in humans probably does not cause significant joint damage. This is in agreement with current clinical evidence (Nissila et al 1978) showing the results of OsO, treatment to be comparable to surgical synovectomy and 'yttrium. A biopsy study (Nissill et al 1977a) in 18 patients 1-18 months after osmium injections showed only minor light microscopic differences compared with controls, although electron microscopy revealed increased amounts of cell debris.…”
Section: Discussionsupporting
confidence: 91%
“…The tentative conclusion from this study then is that Os04 in doses corresponding to those used in humans probably does not cause significant joint damage. This is in agreement with current clinical evidence (Nissila et al 1978) showing the results of OsO, treatment to be comparable to surgical synovectomy and 'yttrium. A biopsy study (Nissill et al 1977a) in 18 patients 1-18 months after osmium injections showed only minor light microscopic differences compared with controls, although electron microscopy revealed increased amounts of cell debris.…”
Section: Discussionsupporting
confidence: 91%
“…Studies comparing Y90 synovectomy to surgical synovectomy or chemical synovectomy with osmic acid show no dierences between these forms of treatment [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…A multicentre trial attempted to resolve this question by comparing Y-90 with triamcinolone hexacetonide but the target patient number was not reached because of problems with recruitment 16. Furthermore, published data show no difference in efficacy between radiation and surgical synovectomy,17 radiation and chemical synovectomy18 and chemical and surgical synovectomy 19…”
mentioning
confidence: 99%